Journal of humanities and applied social science - Jāmiʻat al-Qāhirah (Emerald Publishing Limited, 2019)
The Journal of Humanities and Applied Social Sciences is an academic, peer-reviewed, open access journal focused on the applications of humanities and social science theories and methodologies. Published by Emerald on behalf of Cairo University.
Keywords: Social sciences : Research : Methodology : Periodicals; Humanities : Research : Methodology : Periodicals; Humanities : Research : Methodology; Social sciences : Research : Methodology